Discerning the So-called Abomination in Lev 18:22 and 20:13 in Relation to Holiness, Honour and Shame - Bosman, Hendrik Ludolph (Old Testament Essays, 2023)
Abomination does not appear in the earliest legal collection (Covenant Code) but in Deuteronomy and Deuteronomistic literature, it refers to what is incompatible with YHWH both cultically and ethically in order to maintain the uniqueness of the holy YHWH in the cult and of Israel amongst its neighbours. Abomination is also not used in priestly literature but only in the youngest of the legal collections (Holiness Code). The prohibition of male-male sexual intercourse in Lev 18:22 and 20:13 should be read contextually by relating it to its specific literary and theological-ethical context and not just accepting it as an unconditional legal instruction in general. It is rather a parenetic call to guard against incest as a shaming act that damages the honour of a family. It also entails the rhetorical appeal to the holiness and honour of YHWH as motivation for regulating sexual relations in the family in terms of procreation—procreation not as a timeless creational order but a contextually informed concept that strikes a balance between holiness and honour as well as defilement and shame, informed by the introductory focus on atonement in Lev 16, the reading of Lev 18 during Yom Kippur and the centrality of love for the neighbour and stranger in Lev 19. https://doi.org/10.17159/2312-3621/2023/v36n1a8